Gestão da qualidade no atendimento ao cliente: - Lessas, Pedro Henrique de Freitas (Universidade Federal do Tocantins, 2022)
The article presents some quality management in customer service and verifies that customer service practices, according to the protocol of an Araguaína-TO store, influence the level of customer satisfaction. The survey was conducted in a department store located in the center of the city. The search is qualitative-descriptive, with survey procedures. A questionnaire was applied to the customers of this establishment for the purpose of collecting data to understand which service practices impact customer satisfaction. The questionnaire and divided in four component principals, who are: approach, service, close of the service and exchange of products. The results indicate that the establishment has been creating positive results in customer service practices, but does not satisfy the question "call the customer by name." If you need a more detailed application of the protocol to employees along with the application of training and simulated situations for better instruction and preparation of attendants.